Covid-19 Prevention and Management Policies and Societal Experiences with their Implementation (Kebijakan Pencegahan dan Penanganan Covid-19 dan Implementasinya dalam Pengalaman Masyarakat) - Irianto, Sulistyowati; Nafi, Yvonne Kezia; Prasanthi, Antarin; Cholidah, Ghanies Amany (UI Scholars Hub, 2022)
Abstract The COVID-19 pandemic outbreak has reinforced the need for scientists to collaborate more and more in an interdisciplinary manner, in order to obtain the most comprehensive and appropriate solutions. Covid-19 is indeed the area of medical and health sciences, but this research is carried out comprehensively through the interdisciplinary study of law. The research found that the main problem is in the inconsistent policies and its implementation in preventing and handling the pandemic. The informants, including doctors, show their perspective from their experiences on how the pandemic is a way to deconstruct the whole health problems in Indonesia. Keyword: pandemic Covid-19, law, policy, interdisciplinary study of law, digital survey, digital interview